Low-Complexity Coordinated Relay Beamforming Design for Multi-Cluster Relay Interference Networks - Yang, Zilong; Dong, Min (IEEE transactions on wireless communications, 2019)
Consider a multi-user multi-cluster relay interference network where each cluster contains a source-destination pair communicating through their own dedicated multi-antenna relays. We propose a coordinated relay beamforming design for interference management among relaying clusters, aiming to maximize the minimum signal-to-interference-and-noise ratio (SINR) at destinations, subject to per relay power budgets. We propose a structured relay beam matrix solution based on a weighted sum of two types of beam matrices: zero-forcing (ZF) beamforming and maximum ratio combining (MRC) beamforming, of which we obtain the optimal ZF and MRC beam matrices in closed form. Our proposed beamforming structure allows us to transform the original max-min SINR problem into a low-complexity weight optimization problem, which we solve via the semi-definite relaxation approach. Our solution is highly computationally efficient with the complexity not growing with the number of antennas at each relay. Comparing with the direct approach to obtain relay beam matrices for the original problem, our solution provides a very similar performance but with a significantly lower complexity and thus is scalable and suitable for large-antenna systems. The weights in our relay beamforming solution clearly reveal how the relay power splits and shifts between suppressing inter-cluster interference and maximizing signal beamforming gain as the channel strength or cluster distance changes. The simulation shows that our solution significantly outperforms the MRC-only or ZF-only solution under both the perfect channel-state information (CSI) and imperfect CSI over interference channels.